Thin slices of child personality perceptual, situational, and behavioral contributions. [article]. - Tackett, Jennifer L.
The present study examined whether thin-slice ratings of child personality serve as a resource-efficient and theoretically valid measurement of child personality traits. We extended theoretical work on the observability, perceptual accuracy, and situational consistency of childhood personality traits by examining intersource and interjudge agreement, cross-situational consistency, and convergent, divergent, and predictive validity of thin-slice ratings. Forty-five unacquainted independent coders rated 326 children's (ages 8-12) personality in 1 of 15 thin-slice behavioral scenarios (i.e., 3 raters per slice, for over 14,000 independent thin-slice ratings). Mothers, fathers, and children rated children's personality, psychopathology, and competence. We found robust evidence for correlations between thin-slice and mother/father ratings of child personality, within-and across-tasks consistency of thin-slice ratings, and convergent and divergent validity with psychopathology and competence. Surprisingly, thin-slice and ratings were more consistent across situations in this child sample than previously found for adults. Taken together, these results suggest that thin slices are a valid and reliable measure to assess child personality, offering a useful method measurement beyond questionnaires, helping to address novel questions of personality perception and consistency in childhood. -- (from the authors)